2014 IEEE International Conference on Software Maintenance and Evolution 2014
DOI: 10.1109/icsme.2014.73
|View full text |Cite
|
Sign up to set email alerts
|

On the Impact of Refactoring Operations on Code Quality Metrics

Abstract: Abstract-Refactorings are behavior-preserving source code transformations. While tool support exists for (semi)automatically identifying refactoring solutions, applying or not a recommended refactoring is usually up to the software developers, who have to assess the impact that the transformation will have on their system. Evaluating the pros (e.g., the bad smell removal) and cons (e.g., side effects of the change) of a refactoring is far from trivial. We present RIPE (Refactoring Impact PrEdiction), a techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 5 publications
0
34
0
1
Order By: Relevance
“…This result is quite surprising, given that one of the goals behind refactoring is the removal of bad smells [20]. This finding highlights the need for techniques and tools aimed at assessing the impact of refactoring operations on source code before their actual application (e.g., see the recent work by Chaparro et al [14]). Lesson 4.…”
Section: Conclusion and Lessons Learnedmentioning
confidence: 67%
“…This result is quite surprising, given that one of the goals behind refactoring is the removal of bad smells [20]. This finding highlights the need for techniques and tools aimed at assessing the impact of refactoring operations on source code before their actual application (e.g., see the recent work by Chaparro et al [14]). Lesson 4.…”
Section: Conclusion and Lessons Learnedmentioning
confidence: 67%
“…As we rely on RefactoringMiner to find refactorings performed in the version history of software repositories, it is important to estimate its recall and precision. For this reason, we evaluated RefactoringMiner using the dataset reported in a study by Chaparro et al [5]. This dataset includes a list of refactorings performed by two Ph.D. students on two software systems (ArgoUML and aTunes) along with the source code before and after the modifications.…”
Section: Refactoringminer Precision and Recallmentioning
confidence: 99%
“…In a second study that mined refactorings in 285 GitHub hosted Java repositories, Silva et al [6] found 1,030 false positives out of 2,441 refactorings (63% precision). However, the authors also evaluated Refactoring Miner using as a benchmark the dataset reported by Chaparro et al [21], in which it achieved 93% precision and 98% recall.…”
Section: A Refactoring Minermentioning
confidence: 99%
“…To be able to reliably compute recall, we employed the strategy of building an evaluation oracle by deliberately applying refactoring in software repositories in a controlled manner, similarly to Chaparro et al [21]. Such refactorings were applied by graduate students of a Software Architecture course.…”
Section: Evaluation a Precision And Recallmentioning
confidence: 99%